Reinterpretación bioestratigráfica de los cenoléstidos (Marsupialia) de la región Pampeana: el caso de Pliolestes tripotamicus Reig, 1955 - Deschamps, Cecilia Marcela (2017)
The stratigraphic reinterpretation of a controversial paleontological site such as the Quequén Salado River banks allowed refinement of the biochron of Pliolestes tripotamicus Reig, 1955. Two fossil bearing units were proposed: AUA (Huayquerian) and AUB (Montehermosan). P. tripotamicus found in AUA (but not in AUB, and neither in typical Montehermosan and Chapadmalalan localities) suggests this taxon was not part of the Montehermosan-Chapadmalalan assemblages. P. venetus (Huayquerian), and Pliolestes sp. (Chasicoan) indicate the genus was restricted to the Chasicoan-Huayquerian. The retraction of the cenolestines toward the Andean region (where they live today) would have taken place at the beginning of the Pliocene.